Granular PCM based heat sink for electronics thermal management - Shajahan, Mohamed Iqbal; Benim, Ali Cemal (Pergamon-Elsevier Science Ltd, 2026)
This study investigates aluminum heat sinks integrated with GR42 phase change material (PCM), aiming to enhance thermal inertia and stabilize device temperatures. This is important, since the increasing miniaturization and performance demands for electronic devices have led in a growing need for advanced thermal management systems capable of handling rapid transient loads. The novelty of the work lies in examining different heat sink layouts that optimize the heat dissipation capabilities of GR42 PCMs while minimizing size and weight for electronic cooling. The experimental testing was conducted using three configurations, namely no fin, circular fin and hexagonal fin, with three input powers (4 W, 8 W, and 12 W). The experimental results show that the hexagonal-fin heat sink, surface area is 25 % more than circular fins, exhibited superior thermal performance without significant variation in input power. Notably, the hexagonal-fin heat sink achieved the desired set point temperature of 55 degrees C in 33 % less time than the circular-fin design and 45 % less time than the heat sink without fins. Furthermore, the peak temperatures increased up to 21 % for circular fins. During the charging cycles, the enhancement ratios vary from 72 % and begin to narrow to 25 % during discharge cycles. The hexagonal-fin configuration also exhibited superior melting dynamics, completing the phase transition 44 % faster at higher input power than the circular fins, and established a thermal deviation of nearly 51 % less than finless heat sinks. These findings underscore the critical role of fin geometry and PCM integration in achieving uniform temperature distribution and improved energy storage efficiency. Overall, the hexagonal-fin heat sink with GR42 PCM shows strong potential as a passive cooling solution for low-power portable electronic devices.
Keywords: Heat sinks; Portable electronic cooling; Latent heat storage; GR42 PCM; Hexagonal fin; Circular fin